Analysis of the differences in the 2023 FIFA Women`s World Cup according to match outcome and confederation of origin - López-Araya, S.; Sánchez-Ureña, B.; Gómez-Ruano, M. Á.; Ibáñez, S. J. (International Journal of Performance Analysis in Sport, 2026)
The first Women`s World Cup was held in China in 1991. Its ninth edition was the first tournament to feature 32 teams. Literature on Women`s Soccer continues to grow, but studies on Performance Analysis and Women`s Soccer are still few. The aim of this study was to analyse the Performance Indicators developed in the most recent 2023 FIFA Women`s World Cup. Specifically, the study sought to characterise the game of participating teams and to identify differences based on match outcomes at the group and play-off stages, and according to the confederations of origin. Three mixed linear models were conducted, controlling for the random factor of the participating teams. Significant differences were found based on the match outcome in both offensive and defensive performance, during both the group stage and the play-off stage. In terms of confederations, differences were primarily found in attacking variables between UEFA and the other confederations. The findings of this study highlight the importance of offensive control and enable the analysis of future opponents. It is recommended to increase scientific evidence on Women`s Soccer to enhance sports specificity.